Design and cost performance of decoding technique for hybrid subcarrier spectral amplitude coding-optical code division multiple access system. - Sahbudin, Ratna Kalos Zakiah; Abdullah, M.K.; Mokhtar, Makhfudzah; Hitam, Salasiah; Ahmad Anas, Siti Barirah (Science Publications, 2011)
Problem statement: A hybrid technique combining subcarrier multiplexed and Spectral Amplitude Coding-Optical Code Division Multiple Access (SAC-OCDMA) deploying the Khazani-Syed code was proposed. It was proposed as a mean of increasing the maximum number of simultaneous active users by increasing the subcarrier and/or the SAC-OCDMA code word. Multiple Access Interference (MAI) is the most dominant cause of performance degradation in SACOCDMA systems. Approach: A decoding technique which was simple and easy to build named Spectral Direct Decoding (SDD) technique was proposed for the hybrid system of subcarrier SACOCDMA. Results: The comparison between the complementary subtraction and proposed SDD techniques for hybrid subcarrier SAC-OCDMA system in terms of cost performance was presented here. Results showed that the cost performance of the SDD technique offers a significant improvement over the complementary subtraction detection technique. Conclusion: It is shown that the cost performance of the hybrid system using SDD technique is significantly better than using the Complementary subtraction technique.